Visible light-promoted synthesis of pyrrolidinone derivatives via Rose Bengal as a photoredox catalyst and their photophysical studies. (21st April 2021) - Dutta, Arup; Rohman, Mostofa A.; Nongrum, Ridaphun; Thongni, Aiborlang; Mitra, Sivaprasad; Nongkhlaw, Rishanlang
Abstract : This protocol demonstrates the eco-friendly and sustainable synthesis of pyrrolidinone derivatives using a photocatalyst under irradiation from blue LEDs and their photophysical studies. Abstract : Herein, we report an intramolecular radical cyclization reaction towards the synthesis of pyrrolidinone derivatives via metal-free photoredox catalysis under irradiation from blue LEDs. Some of the remarkable features of this protocol include synthetic efficiency, green reaction profile, easy isolation of products and short reaction time. The photophysical properties of synthesized compounds were investigated via steady state and time-resolved fluorescence spectroscopy in the solid state. Results showed the promising opportunity for their spectral tuning together with large Stokes-shifted and highly active fluorescence emission, thus indicating that these molecular scaffolds can be effective probes for the biological applications and development of opto-electronic devices.